Technostress and its associated factors: Burnout and fatigue among Malaysian healthcare workers (HCWs) in state hospitals. - Nor Asiah Muhamad; Nur Hasnah Ma'amor; Nurul Hidayah Jamalluddin; Izzah Athirah Rosli; Fatin Norhasny Leman; Tengku Puteri Nadiah Tengku Baharudin Shah; Nurul Syazwani Misnan; Norni Abdullah; Mohammad Zabri Johari; Norliza Chemi; Norashikin Ibrahim; Member of Technostress Study (PLoS ONE)
Background Technostress is defined as a psychological state associated with the increased usage of advanced computer technologies on a daily basis. It is also defined as an anxiety feeling or mental strain due to excessive exposure or involvement with technologies. Aim This study aimed to determine the level of technostress associated with burnout and fatigue among healthcare workers (HCWs) in the state hospitals of Malaysia. Methods A cross-sectional study was conducted from September 2022 to November 2023 among HCWs working in the 15-state hospitals in Malaysia. A standardized questionnaire was distributed among the HCWs in the state hospitals in Malaysia. The questionnaire contains information on socio-demography and topic-specific scales on technostress, burnout and fatigue. Results A total of 1620 HCWs were included in the analysis, of which 244 (15%) have high level of technostress, 1089 (67%) have moderate technostress, and 287 (18%) have low technostress. Burnout, and fatigue were significantly associated with technostress. HCWs with moderate burnout were less likely to have high technostress compared to those with high burnout (B =  -0.993, 95% CI; 0.231 - 0.594; p <  0.001). Those with moderate fatigue were less likely to have high technostress (B =  -3.844, 95% CI; 0.003 - 0.162; p <  0.001) compared to those with high fatigue. Conclusions This study found that majority of the HCWs have moderate level of technostress. Technostress has become more common after the COVID-19 pandemic in 2020 drastically altered working conditions and made remote work using information and communication technologies (ICT) a necessity rather than a luxury. Mitigation measures and programs that include psychological support for individuals who are struggling with the technostress and burnout are needed to overcome this issue.